2022
DOI: 10.1111/mpp.13248
|View full text |Cite
|
Sign up to set email alerts
|

Valsa mali secretes an effector protein VmEP1 to target a K homology domain‐containing protein for virulence in apple

Abstract: The K homology (KH) repeat is an RNA‐binding motif that exists in various proteins, some of which participate in plant growth. However, the function of KH domain‐containing proteins in plant defence is still unclear. In this study, we found that a KH domain‐containing protein in apple ( Malus domestica ), HEN4‐like (MdKRBP4), is involved in the plant immune response. Silencing of MdKRBP4 compromised reactive oxygen species (ROS) production and enhanced the suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Inoculating leaves and twigs with mycelium plugs (M1) is a common method of introducing V. mali due to its uniformity [ 29 , 55 ]. Irrespective of its simplicity, fixing mycelial plugs to leaves and stems is a lengthy and time-consuming process.…”
Section: Discussionmentioning
confidence: 99%
“…Inoculating leaves and twigs with mycelium plugs (M1) is a common method of introducing V. mali due to its uniformity [ 29 , 55 ]. Irrespective of its simplicity, fixing mycelial plugs to leaves and stems is a lengthy and time-consuming process.…”
Section: Discussionmentioning
confidence: 99%
“…Under long-night and short-day growing conditions a fly1 knockout mutant, and a FLY artificial microRNA knockdown line, flowered earlier than the wild type ( Dai et al, 2020 ). Yet another study demonstrated that HEN4-like (MdKRBP4), a KH domain-containing protein in apple, is involved in the plant’s immune response ( Wang et al, 2022 ).…”
Section: Eukaryotic Kh Domain Proteinsmentioning
confidence: 99%
“…Previous studies have shown that the effector protein of V. mali plays a very important role in the process of infecting its host, and several effector proteins have been reported [16,17]. For example, the effector protein VmEP1 interacts with host MdPR10 protein, ultimately inhibiting the resistance mediated by MdPR10 against V. mali [18]. Another effector, Vm1G-1794, protects the aggregated MdEF-Tu from autophagic degradation to promote infection in apple [19].…”
Section: Introductionmentioning
confidence: 99%